Influence of product quality brand image and korean brand ambassador NCT dream on decision of customing products mie Lemonilo - Intan Putri Rahayu; Primaraga Sumantri Indra Wicaksana (Institute of Computer Science (IOCS), 2023)
The aim of this study is to analyze the influence partially between Product Quality, Brand Image, and Brand Ambassador on Purchase Decisions in Lemonilo products New Attack. The sample-taking method used by the researchers is nonprobability sampling with the accidental sample method with the number of samples of 100 respondents who are consumers who have purchased Lemonilo in New Attack. The study was conducted using SPSS version 22. To collect data, researchers perform surveys of the spread of questionnaires and library studies. The type of research used is quantitative. The analytical method used is validity test, reliability test, classical assumption test, double linear analysis and hypothesis test. the results of this study are three independent variables namely the quality of the product partially negatively and not significantly affects the purchase decision, but brand image, and brand ambassador partially positively and significantly influences the purchasing decision.